P‐86: High Reliability Flexible OLED Display with Side Seal ALD Film. Issue 1 (June 2015) - Jimbo, Yasuhiro; Tamatsukuri, Yuki; Ito, Minato; Yokoyama, Kohei; Hirakata, Yoshiharu; Yamazaki, Shunpei
Abstract : A flexible organic light‐emitting diode display, fabricated using our transfer technology and provided with high‐quality passivation layers, demonstrates high reliability without being sealed with thick films that reduce productivity. To prevent moisture from entering the sides of the panel, the entire flexible display is coated with an aluminum oxide film using atomic layer deposition. The display survived 500 h of a 65°C, 95%RH preservation test, endured a 100, 000‐time repetitive bending test with a curvature radius of 4 mm, and was found to have a pencil hardness of 4H.